(untitled) (Journal of Asian Development Studies, 2025)
The Sustainable Development Goals (SDGs) provide a comprehensive framework for fostering sustainable development by 2030. In alignment with this global agenda, the Government of Pakistan has implemented various policies and initiatives to localize the SDGs, emphasizing grassroots-level development. This study investigates community perceptions regarding the role of local governments (LGs) in achieving the SDGs, focusing on key areas such as poverty alleviation, education, healthcare, water and sanitation, employment and decent work, and environmental sustainability. A survey was conducted across eight Khyber Pakhtunkhwa, Pakistan districts, gathering data from 400 respondents using a five-point Likert scale. Structural Equation Modeling (SEM) techniques were employed to analyze the data and identify the primary factors influencing public perceptions of LG performance in achieving the SDGs. The research explored economic, social, environmental, and governance dimensions, examining how these factors interact to shape community opinions. Findings reveal a positive correlation between LG initiatives and progress in poverty reduction, education, environmental sustainability, and water and sanitation services. However, the study also highlights negative community perceptions regarding LG’s performance in healthcare delivery and employment opportunities, particularly in terms of providing quality healthcare services and decent work. Based on these insights, the study offers targeted policy recommendations to enhance LG’s effectiveness in achieving the SDGs. These include increased investment in health infrastructure, the expansion of employment programs, measures to strengthen public trust in local governance, and greater community engagement in decision-making processes.